Cultural perspective on religion, spirituality and mental health - Cucchi, Angie; Qoronfleh, M. Walid (Frontiers in Psychology, 2025)
Over the past decade, spirituality and religiosity have gained increasing recognition in the field of mental health, with more individualized approaches emerging. Many mental health professionals have begun integrating aspects of religion and spirituality into their practice and modern psychological therapies have also incorporated principles from ancient Eastern traditions and various worldwide religions. However, these integrations have remained at surface level, assimilating concepts and practices that have been stripped of their ontological framework. The intersection between culture, spirituality and mental wellbeing remains largely underexplored. This can contribute to misunderstandings regarding the conceptualization of mental illness across different cultures and may result in the tokenistic application of ‘culturally sensitive’ interventions, which can perpetuate the disillusionment that some individuals may experience towards mental health services. This cultural perspective paper examines the intersection between culture, religious/spiritual beliefs and mental health. It engages with some of the concepts described above and embodies an anti-colonialist stance, demonstrating the authors’ commitments toward the decolonization of the field of mental health.